Vesicovaginal reflux: A case report - Warade, Monali; Majid, Yameen; Dayananda, L; Gupta, Kanchan (Indian Journal of Radiology and Imaging, 2009)
Vesicovaginal reflux is a common cause of urinary incontinence in girls. A micturating cystourethrogram, which is the diagnostic investigation of choice, can demonstrate retrograde filling of the vagina during micturition and the complete emptying of the vagina at the end of micturition. Vesicovaginal reflux is a rare cause of gross hydrocolpos occurring without any anatomical obstruction. The condition may be associated with functional voiding disturbances.
Keywords: Hydrocolpos; incontinence; micturating cystourethrogram; vesicovaginal reflux; wide bladder neck